Práticas educativas parentais e repertório comportamental infantil: Comparando crianças diferenciadas pelo comportamento - Bolsoni-Silva, Alessandra Turini [UNESP]; Loureiro, Sonia Regina (FapUNIFESP (SciELO), 2011)
Identifying parental practices contingent to the behavior of children is important to support interventions. This study compares parental disciplinary practices with the behavior of children in a clinical group with behavioral problems (n = 27) and of a group of children without behavioral problems (n = 26). The criterion to assign children in the clinical and non-clinical groups was obtained from the Child Behavior Checklist (CBCL). Information concerning parents-children interaction was obtained through the application of the Parental Educative Social Skills Interview Script (RE-HSE-P), which evaluates positive and negative educational practices, context, behavioral problems and children's social skills. Qualitative and quantitative analyses (Mann Whitney's test) were used in the groups' comparison. The results indicate that behaviors that differentiate between the clinical and non-clinical groups are mainly those related to positive educational practices and children's social skills.
Parenting practices and child behavioral repertoire: Comparing children differentiated by behavior
Keywords: Behavior disorders; Childrearing practices; Social interaction